Adaptive Control for Parallel-Connected Energy Storage Converters with Line Parameter Mismatch - Wang, Cheng; Hua, Hongting; Peng, He; Wang, Ze (Frontiers in Energy Research, 2021)
Power electronics interfaced microgrid has become a major trend for modern power systems. In this paper, a three-phase microgrid system formed by multiple distributed energy storages (DES) converters is presented. To improve the reliability and flexibility, DESs are connected in parallel to feed the critical loads, and meanwhile, inject real power to the medium voltage (MV) distributed grid and the local dc bus through an interfacing smart transformer (ST). The ST is working at current control mode while the ac bus voltage is regulated in a sharing way through the DESs. However, due to the physical differences and different environment conditions, filter parameters are not likely to be matched for all the DES modules. Accurate load sharing is therefore the first challenging target. Furthermore, both DES module and ST can fail in event of single-point fault. Fast bus voltage restoring thus becomes the second challenging target. In this paper, the parameter mismatch is considered within the system modeling process. A control framework is then presented in form of a virtual current controller and a backstepping adaptive voltage controller. Adaptive laws are designed to fully compensate for the unknown dynamics within the system transient response. Convergence and boundedness of the signals in the closed-loop control system are demonstrated through rigorous Lyapunov-based stability analysis. Simulation results and experimental results are presented and have demonstrated the effectiveness of the proposed algorithm in terms of both fast bus voltage restoring and accurate power sharing.